2015
DOI: 10.1016/j.stem.2015.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Rho-Signaling-Directed YAP/TAZ Activity Underlies the Long-Term Survival and Expansion of Human Embryonic Stem Cells

Abstract: Human embryonic stem cells (hESCs) can survive and proliferate for an extended period of time in culture, but unlike that of tumor-derived cells, this form of cellular immortality does not depend on genomic aberrations. In this study, we sought to elucidate the molecular basis of this long-term growth property of hESCs. We found that the survival of hESCs depends on the small GTPase Rho and its activator AKAP-Lbc. We show that AKAP-Lbc/Rho signaling sustains the nuclear function of the transcriptional cofactor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
134
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(144 citation statements)
references
References 39 publications
5
134
0
1
Order By: Relevance
“…YAP is believed to be crucial for the self-renewal of embryonic stem cells (Lian et al, 2010;Pan, 2010;Schlegelmilch et al, 2011;Tamm et al, 2011;Liu et al, 2012;Mo et al, 2014;Piccolo et al, 2014;Pijuan-Galito et al, 2014;Varelas, 2014;Yao et al, 2014;Ohgushi et al, 2015). These observations and the high level of YAP in nestin + NSCs led to the hypothesis that YAP might promote NSC self-renewal or proliferation.…”
Section: Normal Nsc Proliferation In Yap-deficient Nscsmentioning
confidence: 99%
See 1 more Smart Citation
“…YAP is believed to be crucial for the self-renewal of embryonic stem cells (Lian et al, 2010;Pan, 2010;Schlegelmilch et al, 2011;Tamm et al, 2011;Liu et al, 2012;Mo et al, 2014;Piccolo et al, 2014;Pijuan-Galito et al, 2014;Varelas, 2014;Yao et al, 2014;Ohgushi et al, 2015). These observations and the high level of YAP in nestin + NSCs led to the hypothesis that YAP might promote NSC self-renewal or proliferation.…”
Section: Normal Nsc Proliferation In Yap-deficient Nscsmentioning
confidence: 99%
“…Upon stimulation, the Hippo pathway subsequently phosphorylates YAP, and phosphorylated YAP undergoes degradation or interacts with 14-3-3 for its cytoplasmic retention. When dephosphorylated, YAP enters the nucleus and interacts with TEAD family proteins to induce the transcription of genes that regulate diverse cellular processes, including cell survival, proliferation and differentiation (Zhao et al, 2007;Lian et al, 2010;Pan, 2010;Schlegelmilch et al, 2011;Tamm et al, 2011;Liu et al, 2012;Yu and Guan, 2013;Mo et al, 2014;Piccolo et al, 2014;Varelas, 2014;Yao et al, 2014;Ohgushi et al, 2015). Although the function of YAP in regulating the development of multiple organs has been investigated, its role in the developing nervous system is less well studied.…”
Section: Introductionmentioning
confidence: 99%
“…Ohgushi and colleagues found that this signaling sustains proliferation, growth and pluripotency of human embryonic stem cells. 31 GNAS protein (Guanine nucleotide-binding proteins G protein) function as transducers in numerous signaling pathways including that involved in the activation of adenylyl cyclases. Iglesias-Bartolome and colleagues evidenced that GNAS-PKA pathway has an important role in promoting proper homeostasis of epithelial stem cells in hair follicle by limiting excessive proliferation that may lead to stem cell exhaustion.…”
Section: Muse Cells Secrete Factors That May Play a Role In Stem Cellmentioning
confidence: 99%
“…The Rho family members RhoA and CDC42 are small GTPases that could modulate cell migration and actin cytoskeleton reorganization [19, 20]. Furthermore, inactivating Rho GTPase could prevent cell migration and cancer cells stemness [21, 22]. Notably, recent research has shown that Up-regulation of GTPBP4 in colorectal carcinoma is responsible for tumor metastasis, and GTPBP4 may disorganize actin cytoskeleton through repressing RhoA signaling [11].…”
Section: Discussionmentioning
confidence: 99%